Effect of High Temperature on Rheology and Electrical Stability of Saraline and Smooth Fluid 05 Mud - Apriandi Rizkina Rangga Wastu; Muhammad Taufiq Fathaddin; Abdul Hamid (Journal of Earth Energy Science, Engineering, and Technology, 2019)
In drilling operations, drilling mud plays a very important role because it is irreplaceable functions. Drilling activities relate to problems caused by complex conditions in formation due to changes in temperature, pressure, and contamination from formation fluids. Using Oil Base Mud (OBM) mud systems in the form of Saraline and Smooth Fluid 05 is tested for drilling fluid performance and the results can be a reference for drilling operation. This research consist of two parts, the first: determining the drilling mud rheology value in the form of (Plastic Viscosity, Yield Point and Gel Strength) in each drilling mud of Saraline and Smooth fluid 05 mud using various high temperature parameters of 350oF, 300oF, and 270oF. The results of the mud rheology tests show at the higher the temperature, the values of rheology decreases. The second experiment is to determine the level of electrical stability in the mud which functions of oil-wet content in oil sludge (Saraline and Smooth fluid 05). The electrical stability value has a minimum limit value in OBM, which is 500 volts. In this experiment showed that the higher the temperature value, the electrical stability value in the mud will decrease, but in this study the value of electrical stability in Saraline mud and Smooth fluid 05 has a value above 500 volts, the composition OBM of Saraline and Smooth Fluid 05 sludge has very good oilwet content.